Synthesis of porous NiO nanocrystals with controllable surface area and their application as supercapacitor electrodes - Subodh Gautam Mhaisalkar (2012)
We report a facile way to grow various porous NiO nanostructures including nanoslices, nanoplates, and nanocolumns, which show a structure-dependence in their specific charge capacitances. The formation of controllable porosity is due to the dehydration and re-crystallization of β-Ni(OH)2 nanoplates synthesized by a hydrothermal process. Thermogravimetric analysis shows that the decomposition temperature of the β-Ni(OH)2 nanostructures is related to their morphology. In electrochemical tests, the porous NiO nanostructures show stable cycling performance with retention of specific capacitance over 1000 cycles. Interestingly, the formation